If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(5 + -1c) = 3(2c + 2) (5 * -4 + -1c * -4) = 3(2c + 2) (-20 + 4c) = 3(2c + 2) Reorder the terms: -20 + 4c = 3(2 + 2c) -20 + 4c = (2 * 3 + 2c * 3) -20 + 4c = (6 + 6c) Solving -20 + 4c = 6 + 6c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-6c' to each side of the equation. -20 + 4c + -6c = 6 + 6c + -6c Combine like terms: 4c + -6c = -2c -20 + -2c = 6 + 6c + -6c Combine like terms: 6c + -6c = 0 -20 + -2c = 6 + 0 -20 + -2c = 6 Add '20' to each side of the equation. -20 + 20 + -2c = 6 + 20 Combine like terms: -20 + 20 = 0 0 + -2c = 6 + 20 -2c = 6 + 20 Combine like terms: 6 + 20 = 26 -2c = 26 Divide each side by '-2'. c = -13 Simplifying c = -13
| -75=3w | | 15y^2-14x^2-90=0 | | 10x+.2= | | x^2+10x-5=9 | | (5.91608)(.5-2x)=(2.5+x) | | 5+7(a+4)=15 | | u^2+14u+15=0 | | (-9+3)(-8+8)(8-1)= | | -11(5)+5(5)= | | (.5-2x)=(2.5+x) | | 10-8(b+2)=7 | | x-(x+8)= | | 48x*3= | | 4x-3+2(x-5)=x | | 9x-22=-46+x | | 8x(5x+3)= | | 13p=2.67 | | 7n=5.55 | | 12m=84.72 | | 5b=63 | | 9x^4*6= | | 4x-21+5w=51 | | 13b+5+2b+4=5b+29 | | -x^3+5x^2+14x=0 | | 2x+3-5x=12 | | 8a+6-5a-3= | | 6x-(3x+4)=x | | 13+6(a+5)=12 | | 42x-7(6x+5)=35 | | 3d+d-7=25/4 | | 3x^2-5x-25=0 | | 0.3y=50.6 |